Study of anticancer and antibacterial activities of Foeniculum vulgare, Justicia adhatoda and Urtica dioica as natural curatives - Batool, R.; Salahuddin, H.; Mahmood, T.; Ismail, M. (Cellular and Molecular Biology, 2017)
High-throughput technologies, such as synthetic biology and genomics have paved new paths for discovery and utility of medicinally beneficial plants. Bioactive molecules isolated from different plants have significantly higher biological activities. The present study was done to analyze antibacterial potential of some medicinal plants against multi drug resistant (MDR) pathogens and anticancer effect against MCF-7 cell line. Methanolic and ethanolic extracts were tested for their antibacterial activity by disc diffusion method against six MDR bacterial strains and for cytotoxicity evaluation by MTT assay. Ethanolic extracts of the three tested plants exhibited growth inhibitory effect against Klebsiella pneumonia, Serratia marcescens and Methicillin-resistant S. aureus. Pseudomonas aeruginosa was more resistant to all extracts as its growth was least inhibited by the extracts of all tested plants. Ethanol extract of Foeniculum vulgare exhibited significant inhibition of cancer cells proliferation. Methanol extract of Justicia adhatoda also showed considerable inhibition of cancer cells. Future studies must converge on detailed investigation of modes of action of extracts of tested plants.